Factors influencing the ESG performance in reducing carbon emission: evidence from China - Zhang, Xueer; Xue, Yaozu (Frontiers in Environmental Science, 2025)
Carbon emission reduction is crucial for high-quality development and realization of China’s “dual-carbon” goal. Based on the data taken from Chinese A-share listed companies from 2013 to 2023, this article examines the effect and mechanism of ESG performance on corporate carbon emission intensity. The results show that high ESG performance has a significant effect on corporate carbon emission reduction, and this conclusion still holds after the robustness test and endogenous analysis. The potential mechanism suggests that ESG performance significantly reduces carbon emission by improving the green technology innovation and total factor productivity. The heterogeneity test indicates that the carbon intensity reduction effect induced by ESG performance improvement is particularly pronounced in manufacturing enterprises, enterprises located in Eastern China, and state-owned enterprises. The results of the study lead to the conclusion that companies should deeply integrate their own strategic blueprints with ESG concepts to improve the level of green technological innovation and total factor productivity, thus promoting China’s accelerated realization of carbon reduction and emission reduction goals.